2021
DOI: 10.1007/s12144-021-01637-3
|View full text |Cite
|
Sign up to set email alerts
|

The need for sense-making as a personal resource: conceptualization and scale development

Abstract: We consider need for sense-making a personal resource and propose that people differ in their levels of this need. We present results of five studies (N = 879) that tested Need for Sense-Making Scale (NSM). The scale is unidimensional, highly reliable, and has satisfactory construct and criterion validity. Need for sense-making was moderately positively related to extroversion, openness, conscientiousness, self-esteem, and sense of control, while negatively related to neuroticism. There was an inverted U-shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Similar to Cantarero et al (2021) we performed diagonally weighted least squares confirmatory factor analysis of the full scale, which supported the unifactorial structure of the scale; the model had a moderate fit to the data χ 2 /df = 5.21; RMSEA = 0.09, 90% CI = [0.083, 0.091], SRMR = 0.10, GFI = 0.93, though χ 2 /df exceeded the recommended 5.00. 2 We next reviewed the content of the items to select a subset for the short version of the scale.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Similar to Cantarero et al (2021) we performed diagonally weighted least squares confirmatory factor analysis of the full scale, which supported the unifactorial structure of the scale; the model had a moderate fit to the data χ 2 /df = 5.21; RMSEA = 0.09, 90% CI = [0.083, 0.091], SRMR = 0.10, GFI = 0.93, though χ 2 /df exceeded the recommended 5.00. 2 We next reviewed the content of the items to select a subset for the short version of the scale.…”
Section: Resultsmentioning
confidence: 64%
“…It is conceptualized as a personal resource as it elevates the chances of achieving a sense of meaning. Cantarero et al (2021) found that need for sense-making related positively to openness to experience, selfesteem, and internal locus of control. Need for sense-making related to searching for meaning in a task, which was linked to perceiving the task as more meaningful and related to better task performance.…”
Section: Individual Differences In Need For Sense-makingmentioning
confidence: 94%
See 1 more Smart Citation
“…Yet, our findings suggest otherwise and are consistent with previous observations. That is, earlier research found similarly small (and null) correlations for need for cognition with boredom (Van Tilburg & Igou, 2016) and with meaning (Cantarero, Van Tilburg, Gąsiorowska, & Wojciszke, 2018). Perhaps, this relatively weak association reflects that need for cognition, which involves a tendency to “engage in and enjoy thinking” (Cacioppo & Petty, 1982, p. 116), occurs in relative isolation of establishing or searching for meaning.…”
Section: Discussionmentioning
confidence: 77%
“…Similar to the participants in our studies, the participants in Chandler and Kapelner's study did not perceive the meaningless condition as more meaningless than the participants in the control condition. This result suggests that evaluations of meaningfulness and meaninglessness may depend upon context, the characteristics of an individual and the relationship between an individual's goals and their actions [9,47].…”
Section: Limitationsmentioning
confidence: 97%